The not so big house : a blueprint for the way we really live - Susanka, Sarah. frey50; Obolensky, Kira. (Newtown, CT : Taunton Press ; [Emeryville, CA] : Distributed by Publishers Group West, 1998)
Provides a review of social trends and their effect on architecture and design.
Keywords: Architecture, Domestic -- Psychological aspects; Space (Architecture); Interior architecture -- Psychological aspects; Architecture domestique -- Aspect psychologique; Espace (Architecture); Architecture interieure -- Aspect psychologique; Architecture, Domestic